Adaptive anti-jamming technologies based on direct sequence spread spectrum and single carrier frequency domain equalization - Fanglin GU; Yuzhen HUANG; Ying ZHAO; Haitao ZHAO; Jibo WEI (Tongxin xuebao)
To solve the performance limitation of direct sequence spread spectrum system in complex multipath environment, an adaptive anti-jamming spread spectrum framework that organically combines single carrier frequency domain equalization (SCFDE) and direct sequence spread spectrum (DSSS) technologies was proposed.The frequency multipath fading was overcame by frequency domain equalization, and the transmission rates and high reliability was reconfigured by deploying variable spread factors.Moreover, the inherent fast Fourier transform process was made full use at the receiver to realize the adjoint detection and analysis of interference intensity, interference type and other information, etc.Then, the frequency domain bearing point online was optimized and selected to improve the adaptability to the interference, especially blocking interference.The simulation results show that the proposed direct spread spectrum waveform based on SCFDE has good communication performance in both Gaussian and multipath environments, and the notch of some frequency bands has little impact on the communication performance, which verifies the effectiveness of anti-jamming by adaptive optimizing information frequency domain bearers.